(untitled) (Chittagong University Journal of Biological Sciences, 2013)
Petroleum ether, chloroform, ethyl acetate and carbon tetrachloride extracts of Moringa oleifera stem bark were studied for their antimicrobial activities against eleven human pathogenic bacteria (Shigella dysenteriae, S. sonnei, Salmonella typhi, S. paratyphi, Bacillus subtilis, B. megaterium, B. cereus, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Vibrio cholerae) and four human pathogenic fungi (Aspergillus niger, A. ochraceus, A. ustus and Candida albicans) using disc diffusion and poisoned food method, respectively. Chloroform and ethyl acetate extracts exhibited moderate to good antibacterial and antifungal activity against all the pathogens tested. The ethyl acetate extract exhibited the largest zone of inhibition (21 mm in diameter with 2000 mg/disc extract) against S. sonnei. The highest inhibition of fungal radial mycelial growth (52. 00% with 100 mg extract/ml medium) was recorded against C. albicans with ethyl acetate extract. The ethyl acetate extract exhibited the lowest MIC (750 mg/ml) against B. megaterium, S. dysenteriae, V. cholerae and E. coli. For fungi, the lowest MIC was 500 mg/ml against C. albicans with crude extract of ethyl acetate. DOI: http://dx.doi.org/10.3329/cujbs.v3i1.13411 The Chittagong Univ. J. B. Sci.,Vol. 3(1&2):109-117, 2008